Marriage in Andean oral tradition - Murguía-Sánchez, Luis Ernesto (2024)
The work presents an approach to the study of marriage in the oral record of the Andean highlands of Peru and aims to develop an exegesis of the mediations and scope of the oral source: the marriage of the atoq or fox with the maidenin Quechua society. Next, the terms that give rise to the links between the oral and written records are investigated, to then identify what they communicate or suggest, in order to understand the world they create and the challenges they face. The method employed prioritizes ethnographic and interpretive approaches to approximate the various levels ofmeaning and "interpret the interpreted." The conclusions indicate, on the one hand, that the oral source is the greatest device of collective memory, as it unites generations to make them endure over time.